“Gestión de residuos sólidos y educación ambiental de los comerciantes del mercado del río de Quevedo. año 2020.” - Avilés Alcívar, Andrea Aydee (2020)
The research was carried out in the “Mercado del Rio” located in the Quevedo Canton, whose objective was to evaluate the management of solid waste and the educational level, in terms of environmental education of the merchants, the inductive and deductive method was used using the analysis of the interview, direct observation and analysis of the information. It was established that there is no rigorous supervision in the handling of food and in the management of waste generated in the market, being a focus of contamination of the environment causing food to reach consumers, there are no guidelines to follow for its constant training. and improvement in the aforementioned aspects, the daily average collected by commercial premises is six kilograms, of which 4.1 kg corresponds to organic (68%) and 1.9 kg (32%) to inorganic ones. The waste collection is assisted by the private company Innova S.A, currently it does not have differentiated collection, so the waste generated in the market is deposited in a common container. The Manual of Healthy Markets of Ecuador, allowed determining that the market has shortcomings especially in the areas of infrastructure, services, health, training, pest control, food handling, control and assurance of safety, utensils, acquisition, marketing, transportation , reception and storage of food, an immediate solution is required, so through the proposal of the environmental education program these deficiencies for the river market could be improved, the same as its initial conception, will be transmitted to the managers of the Public Company of Municipal Markets of the Quevedo Canton. Key words: Solid Waste Management - Environmental education - Market - Traders